Primary Productivity of the Brackishwater Impoundments along Nethravathi estuary, Mangalore in Relation to Some Physico-chemical Parameters - K.M., Rajesh; G., Gowda; Mendon, Mridula R. (Fishery Technology, 2025)
Primary productivity of brackishwater impoundments along Nethravathi estuary was studied for one year from Feb. 1998 to Jan. 1999. The primary productivity values varied from 1.78 to 13.47 mgC/m3/h and it exhibited a bimodal pattern of distribution with primary peak in May followed by a secondary peak in September. Lower values were recorded during monsoon season (June-Aug). Chlorophyll-a values observed to range from 2.83 to 9.71 mg/ m3 with higher values recorded during monsoon season and lower values in the month of Dec/Jan. The seasonal trend of phaeopigment exhibited trimodal peak during March, November and July.